Experience Control Analysis of English Reading Software Based on Wireless Binocular Line-of-Sight Sensing - Cheng Feng (Hindawi Limited, 2021)
This paper proposes a segmented combined English text measurement method based on two sets of orthogonal linear image sensors and one area image sensor. This method fully combines the advantages of the linear image sensor and the area image sensor in long-distance and short-distance English text measurement and can continuously perform high-precision English text tracking within a large range of viewing distance. Based on this method, a set of segmented English text measurement system is designed and constructed. This paper presents a method for extracting English word boundaries based on semantic segmentation to solve the problem of global positioning and horizontal initialization of English reading text. The semantic segmentation method based on fully convolutional networks (FCN) is analyzed, and the target classification is defined. We used the classic FCN framework and model, fine-tuned with manually annotated data, and achieved good segmentation results. For the definition and extraction of English word boundaries in English text, a piecewise linear model is used to measure the projection confidence of each English word boundary point, and the overall observation of the English word boundary is measured. When the observation confidence is high enough, combined with the English word boundaries marked in the high-precision image, the horizontal positioning is obtained by matching the weights. This paper concludes that English reading software can help learners in English learning to a certain extent, which proves that the English reading software is an effective supplement based on blended learning classrooms. Through the analysis of learners and teaching content, an English teaching model based on English reading software blended learning is designed. Experimental studies have proved that English reading software can help learners learn English, which not only expands their vocabulary but also broadens their horizons.